Pulmonary adenocarcinoma: implications of the recent advances in molecular biology, treatment and the IASLC/ATS/ERS classification - Revannasiddaiah, Swaroop; Thakur, Priyanka; Bhardwaj, Bhaskar; Susheela, Sridhar Papaiah; Madabhavi, Irappa (Journal of Thoracic Disease, 2014)
A decade ago, lung cancer could conveniently be classified into two broad categories—either the small cell lung carcinoma (SCLC), or the non-small cell lung carcinoma (NSCLC), mainly to assist in further treatment related decision making. However, the understanding regarding the eligibility of adenocarcinoma histology for treatments with agents such as pemetrexed and bevacizumab made it a necessity for NSCLC to be classified into more specific sub-groups. Then, the availability of molecular targeted therapy with oral tyrosine kinase inhibitors (TKIs) such as gefitinib and erlotinib not only further emphasized the need for accurate sub-classification of lung cancer, but also heralded the important role of molecular profiling of lung adenocarcinomas. Given the remarkable advances in molecular biology, oncology and radiology, a need for felt for a revised classification for lung adenocarcinoma, since the existing World Health Organization (WHO) classification of lung cancer, published in the year 2004 was mainly a pathological system of classification. Thus, there was a combined effort by the International Association for the Study of Lung Cancer (IASLC), the American Thoracic Society (ATS) and the European Respiratory Society (ERS) with an effort to inculcate newly established perspectives from clinical, molecular and radiological aspects in evolving a modern classification for lung adenocarcinomas. This review provides a summary of the recent advances in molecular biology and molecular targeted therapy with respect to lung adenocarcinoma. Also, a brief summation of the salient recommendations provided in the IASLC/ATS/ERS classification of lung adenocarcinomas is provided. Lastly, a discussion regarding the future prospects with lung adenocarcinoma is included.